ANALYTICAL FACTORS THAT AFFECTING THE STUDENT SATISFACTION IN UNIVERSITY OF SINGAPERBANGSA KARAWANG, INDONESIA - Fifi Franto (Value : Journal of Management and Business, 2019)
This mini research aims to analyze the factors that influence student satisfaction with the educational services in University of Singaperbangsa Karawang (UNSIKA), a case study of students in University of Singaperbangsa Karawang. The data were primary data and processed using factor analysis. The samples studied were 340 cross-study students at UNSIKA. The variables studied were 1 variable. There are 5 sub-variables with 16 indicators. These data are proceed by using SPPS 24 version.                The result of this research shows that the result of 5 sub-variables with 16 indicators analyzed with the model of factor analysis that influences the student satisfaction in UNSIKA includes 4 factors, that are The Clean of the classroom, The Match between the fees and the facilities, UNSIKA image and The Academic services